Two new species of Astata Latreille from Iran (Hymenoptera, Astatidae) - Jacobs, Hans-Joachim; Rezaei, Shohreh; Fallahzadeh, Majid (Zootaxa, 2023)
Two new digger wasp species of the genus Astata Latreille, 1796 (Hymenoptera, Astatidae), A. ljubomirovi sp. nov. and A. rubriventris sp. nov. are described from Iran. Moreover, A. compta Nurse is newly recorded from the Palaearctic region and Iran, redescribed and illustrated. Diagnostic characters and key features to each species are given. With the present additions, the total number of Astata recorded from Iran increases up to 14.